99m-Tc-MDP-Scintimammography in the evaluation of breast masses or tumor angiogenesis - (:unkn) unknown (My University, 2004)
BACKGROUND: Vascular endothelial growth factor (VEGF) is a prognostic factor in breast cancer. One of the mechanisms of extra-skeletal uptake of Tc-99m-methylenediphosphonate (MDP) is suggested to be tumor vascularity. We studied the correlation between MDP uptake and VEGF and compared the diagnostic accuracy of mammography versus MDP-scintimammography (MDP-S). MATERIALS AND METHODS: Fifty-four patients with suspicion of breast cancer were evaluated. Breast images were collected 5-10 minutes after injection of Tc-99m-MDP prior to biopsy. Tissue slides were stained using a rabbit-polyclonal anti-VEGF. RESULTS: MDP-S showed a diagnostic accuracy of 83.3% in BIRADS category 4 lesions. Four out of 23 benign lesions were false-positive. The tumor to background (TM/BG) ratio of early images of MDP-S was correlated with VEGF staining (p: 0.014) and with tumor size (p: 0.006). CONCLUSION: Early images of Tc-99m-MDP-S may satisfactorily identify cancers with increased neovascularization. MDP-S seems to be an accurate imaging modality, especially in BIRADS category 4 lesions.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Aged, 80 and over; Vascular Endothelial Growth Factor A; Radionuclide Imaging; Radiopharmaceuticals; Breast Neoplasms; Neovascularization, Pathologic; Mammography; Technetium Tc 99m Medronate